Reply [to comments on "Testing the Lucas Critique: A Review"] - Favero, C; Hendry, D (Taylor and Francis, 1992)
We are grateful to Grayham Mizon and Roger Farmer for their comments on our review of the Lucas Critique (see Farmer, Roger E.A.(1992) A comment on "Testing the Lucas Critique: A review". Econometric Reviews, v.11, iss.3, p. 307-311 http://dx.doi.org/10.1080/07474939208800239 and Grayham, E. Mizon (1992) Comment. Econometric Reviews, v.11, iss.3, p.313-316 http://dx.doi.org/10.1080/07474939208800240 )